2021
DOI: 10.2147/jpr.s312224
|View full text |Cite
|
Sign up to set email alerts
|

Nomograms for Predicting Recurrent Herniation in PETD with Preoperative Radiological Factors

Abstract: To investigate the preoperative radiological risk factors for recurrent lumbar disc herniation (rLDH) within 1 year after percutaneous endoscopic transforaminal discectomy (PETD). Patients and Methods: A retrospective case-control study was conducted. Between January 2013 and November 2019, a total of 1210 patients with single-level L4/5 LDH who underwent PETD were enrolled in the present study. In total, 62 rLDH patients were diagnosed and collected based on the clinical and radiological manifestations, and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 32 publications
1
21
2
Order By: Relevance
“…However, as is discussed above, this influence may not be as significant in geriatric DLSS patients. This conclusion is consistent with other previous findings (20,44). Notably, due to the mechanical defect, patients with Modic changes, especially type 1, have a trend of deterioration in postoperative back pain, in which endoscopic procedures may be less effective (45).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, as is discussed above, this influence may not be as significant in geriatric DLSS patients. This conclusion is consistent with other previous findings (20,44). Notably, due to the mechanical defect, patients with Modic changes, especially type 1, have a trend of deterioration in postoperative back pain, in which endoscopic procedures may be less effective (45).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, in this study we focused on the radiological characteristics, which are relatively objective indicators, and the influence of demographic characteristics on reoperation was decreased by matching. However, previous studies have proposed that risk factors might differ among subgroups (20).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies have reported a variety of complications, such as recurrence of LDH (rLDH), incomplete decompression, nerve root injury, dural tear, visceral injury, nerve root induced hyperalgesia or burning-like nerve root pain, postoperative dysesthesia, intraoperative seizure, posterior neck pain, surgical site infection, and instrument breakage, in the treatment of LDH using PELD [ 1 , 2 , 12 – 14 ]. In addition, these complications are associated with multiple factors, including rLDH-related risk factors, such as obesity, old age, Modic changes, low grade of surgical-level disc degeneration, high disc height index (DHI), large sagittal range of motion, and severe grade of adjacent-level disc degeneration [ 15 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment improvement rate score ( 18 , 19 ) for the lumbar spine JOA score at 1 year after TMD: The lumbar spine JOA score method at 1 year after the operation was the same as that before the operation, and the treatment improvement rate was =[(post-treatment score—pre-treatment score) ÷ (full score 29—pre-treatment score)] × 100%. The improvement rate reflects the improvement of the lumbar spine function of the patient before and after treatment to evaluate the clinical efficacy: a cure rate of 100% was considered as cure, an improvement rate of more than 60% was considered as markedly effective, 25%–60% was considered as effective, and less than 25% was considered invalid.…”
Section: Methodsmentioning
confidence: 99%